Foot and ankle sports medicine - Altchek, David; DiGiovanni, Christopher W.; Dines, Joshua S.; Positano, Rock G. (Online access: Ovid Technologies LWW Doody's Core Collection 2019., 2013)
"With this brand new book, sports medicine practitioners will have one of the most comprehensive and practical resources for the treatment of foot and ankle sports injuries. In addition to tendon disorders, trauma, hindfoot, midfoot, forefoot, and lower leg, this books 32 chapters also cover pediatric sports injuries, sport specific injury prevention, rehabilitation, and even shoe selection. Over 40 specialists in orthopaedic surgery, podiatry, physiatry, physical therapy, and athletic training contributed to this books content. Including team physicians, physical therapists, and athletic trainers for major sports teams including the New York Giants, New York Mets, Philadelphia Flyers, Philadelphia Eagles, New York Knicks, Washington Nationals, Carolina Panthers, and the US Davis Cup Tennis team. It's the combination of all these different disciplines that makes this book a resource for treatment of foot and ankle sports injuries"--Publisher's description